2006
DOI: 10.2215/cjn.01050306
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Advance Care Planning for Patients with End-Stage Renal Disease

Abstract: Comprehensive care of patients with ESRD requires expertise in advance care planning (ACP), including attention to ethical, psychosocial, and spiritual issues related to starting, continuing, withholding, and stopping dialysis. However, there are no standards of care regarding when to initiate or how to facilitate ACP. The purpose of this study was to determine the perspectives of patients with ESRD of the salient elements of ACP discussions. An ethnographic, qualitative, in-depth interview study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(211 citation statements)
references
References 24 publications
9
188
0
14
Order By: Relevance
“…21 Life expectancy is often important in shaping treatment preferences. 22 However, in older patients with severe chronic illness and limited life expectancy, maximizing survival may be but one of several competing treatment goals. Patients may be faced with tradeoffs between prolonging life and optimizing other goals, such as preserving dignity, maximizing comfort, and maintaining quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…21 Life expectancy is often important in shaping treatment preferences. 22 However, in older patients with severe chronic illness and limited life expectancy, maximizing survival may be but one of several competing treatment goals. Patients may be faced with tradeoffs between prolonging life and optimizing other goals, such as preserving dignity, maximizing comfort, and maintaining quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…69,135 Relatives clearly have an important role to play in decisions about ACP and in providing hands-on care for patients dying at home. 133,136 However, carers' entitlement to information about prognosis and their role in decision-making and future planning is frequently unclear, and carers assess professional communication about EOLC as inadequate. 100 Evidence for effectiveness of advance care planning Despite the very considerable policy commitment to ACP in the UK as well as internationally, it remains uncommon in practice.…”
Section: 114mentioning
confidence: 99%
“…Previous research has shown that patients prefer end-of-life care discussions to be initiated by their physicians [19], and that lack of physician initiative is one of the biggest barriers to advance care planning [20,21]. Differences between the physician and patient likely contribute to this barrier.…”
Section: Discussionmentioning
confidence: 99%